2019
DOI: 10.3349/ymj.2019.60.4.352
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanism of MicroRNA-145 in the Pathogenesis of Acute Aortic Dissection

Abstract: PurposePrevious studies have confirmed that microRNAs play important roles in the pathogenesis of acute aortic dissection (AAD). Here, we aimed to explore the role of miR-145 and its regulatory mechanism in the pathogenesis of AAD.Materials and MethodsAAD tissue samples were harvested from patients with aortic dissection and normal donors. Rat aortic vascular smooth muscle cells (VSMCs) were transfected with miR-145 mimic/inhibitor or negative control mimic/inhibitor. Gene and protein expression was measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…In cardiovascular diseases, the miR-143/145 cluster is the best studied miRNA cluster. Indeed, miR-145 and miR-143 are widely involved in cardiovascular diseases, such as atherosclerosis, coronary heart disease, aortic dissection, valvular disease, and pulmonary hypertension ( Caruso et al, 2012 ; Liu et al, 2013 , 2019 ; Guo et al, 2016 ; Girdauskas et al, 2018 ; Shi et al, 2018 ; Sun et al, 2018 ; Yue et al, 2018 ; Li T. et al, 2019 ; Vacante et al, 2019 ). Deng et al (2015) reported that exosomal miR-143 regulates the interaction between VSMCs and endothelial cells in PAH.…”
Section: Cardiovascular Diseases and Exosomal Mirnasmentioning
confidence: 99%
“…In cardiovascular diseases, the miR-143/145 cluster is the best studied miRNA cluster. Indeed, miR-145 and miR-143 are widely involved in cardiovascular diseases, such as atherosclerosis, coronary heart disease, aortic dissection, valvular disease, and pulmonary hypertension ( Caruso et al, 2012 ; Liu et al, 2013 , 2019 ; Guo et al, 2016 ; Girdauskas et al, 2018 ; Shi et al, 2018 ; Sun et al, 2018 ; Yue et al, 2018 ; Li T. et al, 2019 ; Vacante et al, 2019 ). Deng et al (2015) reported that exosomal miR-143 regulates the interaction between VSMCs and endothelial cells in PAH.…”
Section: Cardiovascular Diseases and Exosomal Mirnasmentioning
confidence: 99%
“…Another study reported that the miR‐145 expression level is consistent with the mortality of patients with AD. Increased miR‐145 expression can accelerate VSMC proliferation and ameliorate cell apoptosis by binding to SMAD3 and connective tissue growth factor (CTGF), which can reduce the effect of miR‐145 in the progression of AAD 20 . CTGF, a matricellular protein, can ameliorate aortic remodelling in the rat AD model and participate in the proliferation and apoptosis of VSMCs 68 .…”
Section: Mirnas In Aortic Dissectionmentioning
confidence: 99%
“…Particularly, numerous studies have reported that non‐coding RNAs (ncRNAs) play a significant role in the development of cardiovascular diseases, such as atherosclerosis, restenosis after stent and aneurysm 14‐18 . Likewise, several reports have suggested that ncRNAs also play a crucial regulatory role in the occurrence and development of AD 19‐21 . In this review, we discuss the role of ncRNAs and their target genes, as well as their regulatory mechanisms in AD.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, several miRNAs have been con rmed to be closely involved in cardiovascular diseases and even maybe a new strategy for the diagnosis, therapy, or prediction in cardiovascular diseases. Certain miRNAs, such as miRNA-21 [7], miRNA-134-5p [8], miRNA-145 [9], miRNA-146b [10], have been reported to play de nite roles in the development of AD.…”
Section: Introductionmentioning
confidence: 99%